2022
DOI: 10.3390/plants11152012
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Four Essential Oils Extracted from Chilean Patagonian Plants as Potential Organic Pesticides

Abstract: Patagonia is a geographical area characterized by a wide plant biodiversity. Several native plant species are traditionally used in medicine by the local population and demonstrated to be sources of biologically active compounds. Due to the massive need for green and sustainable pesticides, this study was conducted to evaluate the insecticidal activity of essential oils (EOs) from understudied plants growing in this propitious area. Ciprés (Pilgerodendron uviferum), tepa (Laureliopsis philippiana), canelo (Dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For the above reason, there has been a growing global interest in eco-friendly pesticides, including those produced by plants [5][6][7]. Among botanical products, essential oils (EOs) could play a fundamental role in the agrochemical industries, and they have been widely studied against many arthropod pests [8][9][10][11]. EOs showed different modes of action, such as antifeedant, repellent, or deterrent activities, and they can be useful as larvicide, ovicide, and adulticidal agents.…”
Section: Introductionmentioning
confidence: 99%
“…For the above reason, there has been a growing global interest in eco-friendly pesticides, including those produced by plants [5][6][7]. Among botanical products, essential oils (EOs) could play a fundamental role in the agrochemical industries, and they have been widely studied against many arthropod pests [8][9][10][11]. EOs showed different modes of action, such as antifeedant, repellent, or deterrent activities, and they can be useful as larvicide, ovicide, and adulticidal agents.…”
Section: Introductionmentioning
confidence: 99%
“…These metabolites, accumulated in different parts of the plant, are components of plant extracts or essential oils (EOs) and frequently manifest toxicity, act as antifeedants through pest metabolism alternation and fitness reduction, or simply deter or repel insect pests [ 10 , 11 , 12 ]. EOs, as complex mixtures of volatile compounds, have been shown to display insecticidal properties against various pests [ 13 , 14 , 15 ]. They are already recognized as potential biopesticides involved in sustainable agriculture [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], but with challenging requirements to adapt results from laboratories to fluctuating outdoor conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among botanical products, EOs could be potential candidates for the development of novel biopesticides and insecticides. In previous studies, we showed that numerous EOs could display their insecticidal and pesticidal potential towards different insect species depending on the synergistic or antagonistic effect of their components that revealed suitable LC 50 and LC 90 values [25][26][27].…”
Section: Introductionmentioning
confidence: 99%